Integrative Humanities Education: Japan’s Interdisciplinary Curriculum Reform and Its Implications for Global Educational Paradigms - Habib Badawi (IQRO: Journal of Islamic Education, 2026)
This study investigates the effectiveness of Japan’s integrated secondary humanities curriculum—combining history, geography, ethics, and social sciences—in fostering critical thinking, cultural competence, and holistic understanding. Employing a convergent parallel mixed-methods design, the study engaged 500 high school students (ages 15–18) and 50 teachers across ten purposively selected schools representing diverse urban, rural, and socioeconomic contexts in Japan. Quantitative findings demonstrated statistically significant gains in critical thinking (Watson-Glaser Appraisal: d = 0.71, p < .001) and cultural competence (Cultural Intelligence Scale: d = 0.84, p < .001), alongside a 9% average improvement in overall GPA. Qualitative analysis—drawing on semi-structured interviews, classroom observations, focus groups, and reflective essays—revealed enhanced interdisciplinary reasoning, improved perspective-taking, and heightened student motivation, while identifying teacher professional development as a key implementation challenge. These findings affirm the viability of constructivist, interdisciplinary curriculum models for preparing secondary students for globalized society and offer transferable insights for educational reform in comparable national contexts.